A New Practice to Monitor the Fabrication Process of Fab-Targeting Ligands from Bevacizumab by LC-MS: Preparation and Analytical Characterization - Franck Marquet; Valentina D'Atri; Davy Guillarme; Gerrit Borchard (MDPI AG, 2022)
The objective of this study was to qualitatively evaluate a Fab-targeting ligand preparation containing free thiol groups in the hinge region by using bevacizumab as a model. The evaluation focused on the purification of fragments through a nonaffinity-based process using a centrifugal ultrafiltration technique and mild reduction conditions for the intact production of F(ab') fragments with specific inter-heavy-chain disulfide bonds cleavage. Under these conditions, F(ab') fragments with a defined chemical composition were successfully obtained via proteolytic digestion followed by a controlled reduction reaction process maintaining the integrity of the binding sites. The ultrafiltration purification technique appears to be suitable for the removal of the digestive enzyme but inefficient for the removal of Fc fragments, thus requiring additional processing. A suitable analytical strategy was developed, allowing us to demonstrate the reformation of disulfide bridges between the two reduced cysteines within F(ab') fragments.